The Effect of Sugar Dose and Fermentation Time on the Quality of Sauerkreut as a Source of Probiotic - Ari, Ari Andani Nasution; Trisna, Ade; Julianti, Elisa (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study aims to determine the effect of sugar dosage and fermentation time on the quality of sauerkraut as a source of probiotics. This study used an experimental method in a 3x3 factorial completely randomized design (CRD). The first factor is three treatments of sugar concentration (A), namely A1 (2%), A2 (3.5%), and A3 (5%). The second factor is three treatments of fermentation time (B), namely B1 (5 days), B2 (7 days), and B3 (9 days). The results showed that there was no interaction (P>0.05) between factor A and factor B in the water content, but the water content had a significant effect (P<0.05) separately in factor A and factor B. In total LAB, there was a very significant interaction (P<0.01) between factor A and factor B, and in factor A and factor B. In pH, there was a significant interaction (P<0.05) between factor A and factor B, but a very significant effect (P<0.01) in factor A and factor B. In acid content there was a significant interaction (P<0.05) between factor A and Factor B, but a very significant effect (P<0.01) on factor A and factor B. This study concludes that cabbage processed into sauerkraut can be used as a probiotic supplement. The addition of 3.5% sugar and 7-day fermentation resulted in 91.11% water content, 3.43 pH, 2.93% total acid, and 7.4 x 109 total LAB